Pan-cancer analysis of Arp2/3 complex subunits: focusing on ARPC1A’s role and validating the ARPC1A/c-Myc axis in non-small cell lung cancer - Zhou, Chenkang; Chen, Yuxin; Chen, Shuhui; Hu, Lijuan; Wang, Junjun; Wang, Yumin (Frontiers in Immunology, 2025)
BackgroundThe Arp2/3 complex is a key regulator of tumor metastasis, and targeting its subunits offers potential for anti-metastatic therapy. However, the expression profiles, prognostic relevance, and diagnostic value of its subunits across cancers remain poorly understood. This study aims to investigate the clinical relevance of Arp2/3 complex subunits, particularly ARPC1A, in pan-cancer, and to further analyze the potential biological mechanisms of ARPC1A, as well as its association with immune infiltration and chemotherapy drug sensitivity.MethodsTo explore the differential expression of Arp2/3 complex subunits and their clinical relevance across cancers, we analyzed data from TCGA and GTEx databases. The relationship between ARPC1A and immune infiltration, as well as its interactions with functional proteins, was examined using the TCPA and TIMER2.0 databases. Gene Set Enrichment Analysis (GSEA) was performed to identify ARPC1A-associated signaling pathways. Chemotherapy drug sensitivity correlated with ARPC1A expression was assessed using CellMiner, GDSC, and CTRP databases. The effect of ARPC1A on c-Myc expression was validated by quantitative PCR (qPCR) and Western blot. Finally, the biological role of ARPC1A in non-small cell lung cancer (NSCLC) cells was further validated using CCK-8, EdU incorporation, colony formation, and Transwell assays.ResultsThe Arp2/3 complex subunits, particularly ARPC1A, are frequently overexpressed in a majority of cancers, correlating with poor prognostic outcomes and demonstrating significant diagnostic utility. Copy number variations may play a role in the dysregulation of Arp2/3 complex subunit expression. The small molecule X4.5.dianilinophthalimide has shown promise as a targeted therapeutic agent in a pan-cancer context. Functional predictions indicate that ARPC1A is implicated in oxidative phosphorylation pathways and cell proliferation-related signaling pathways, including those mediated by MYC, with ASNS potentially acting as an upstream regulator. Furthermore, ARPC1A has been implicated in the resistance to chemotherapy drugs, including gefitinib. In vitro experiments corroborate that ARPC1A may enhance malignant phenotypes in non-small cell lung cancer (NSCLC) cells through the regulation of c-Myc expression.ConclusionOur study offers novel insights into targeting Arp2/3 complex subunits as an anti-cancer strategy and underscores the potential of ARPC1A as a novel biomarker for tumor diagnosis, prognosis, and the prediction of immune therapy responses.